Sources and conditions for the formation of Jurassic post-orogenic high-K granites in the Western Guangdong Province, SE China - Huang, Hui-Qing (Curtin University, 2012)
High-K granites have become volumetrically important since at least Proterozoic. Their study bears important implications to crustal and tectonic evolutions. Despite of intensive research, sources and conditions for the formation of high-K granites remain controversial, mainly resulted from the uncertainty regarding the magmatic evolution. Thus, to understand the origin of compositional variations in granite suites is fundamental for granite research.Several petrogenetic models have been proposed to account for the mineralogical and chemical variations of granites, with each individual model bearing different implications to the origin of granitic magmas and the crustal evolution. In this study, Jurassic high-K granites in the western Guangdong Province of SE China are systematically studied for their geochronology, petrography, mineralogy, whole-rock geochemistry, whole-rock Sr-Nd isotope compositions, and in-situ zircon Hf-O isotopes. Their petrogenetic processes are then examined using these results as well as existing information for the exploration of sources and conditions for the extensive post-orogenic granitic magmatism in the Jurassic South China. Crustal evolution of the basement terranes in this region is also discussed.Granites with features typical of A-type, I-type or S-type were formed during ~165−155 Ma in the study area. A-type granitic rocks from the Jiuyishan granite suite contain anhydrous ferromagnesian minerals fayalite and ferrosilite, implying low water activity and oxygen fugacity (fO2<FMQ buffer) in their source rocks and high temperature for partial melting. Chemical and isotopic variations documented in the Jiuyishan A-type suite could be best explained using processes of fractional crystallization. Evolved radiogenic (whole-rock: ISr = 0.7151–0.7181, εNd(t) = -9.3 to -6.4; zircon: εHf(t) = -8.2 to -2.3) and high oxygen isotope compositions (δ18Ozircon = 6.3‰−11.5‰) suggest that the Jiuyishan A-type granite was most likely derived from high temperature (>960 ºC) melting of granulitic metasedimentary rocks, with no or very limited contribution of mantle-derived materials.Mineralogical, geochemical and isotopic results suggest that the Jiufeng granite as well as the Dadongshan granite was dominantly sourced from metasedimentary rocks (S-type), too, but at lower melting temperatures (~820 ºC). Different from the Jiuyishan A-type granite, chemical variations exhibited by the Jiufeng granite samples could not be a result of magma differentiation (with or without wall-rock assimilation), but were most likely inherited from the heterogeneous source region, with sporadic local magma mixing. Where the contribution of mantle-derived materials was significant, the rocks show mineralogical (e.g., hornblende-bearing) and geochemical (e.g., A/CNK <1) features similar to I-type granites.Some other granites with typical I-type features have been intruded as stocks along the southern coastal area of the western Guangdong Province. They however show less 18O and 87Sr (but more 143Nd and 176Hf) enrichment than the Jiufeng I-type granite samples (δ18Ozircon: 6.3‰−7.9‰ vs. 7.5‰−8.8‰; ISr: 0.7057−0.7077 vs. 0.7125−0.7143). The granites, particularly those with high oxygen fugacities (fO2 >NNO; e.g., the Gangwei and Lunshui), could have been generated by direct melting of high-K basaltic rocks. It is noted that even such granites contain contribution of supracrustal materials that were probably inherited from their source rocks.Results obtained in the course of this research are consistent with those from experimental studies. Jurassic post-orogenic high-K granites in SE China are characterized by not only their high K2O contents and K2O/Na2O ratios (>1), but also their enrichment in 18O and 87Sr. This work suggests that granites like these could be simply derived from dehydration melting of metasedimentary rocks, while those with high oxygen fugacities and mantle-like isotope compositions could also be generated by melting oxidized hydrous high-K basaltic-intermediate igneous rocks. Therefore, the seemingly well constructed mixing line exhibited by zircon Hf-O isotopes is most likely resulted from secular reworking of supracrustal materials by mantle-derived magmas to variable degrees, but not an instant result of magma mixing. In spite of this, Nd isotope model ages of 2.0−1.2 Ga of these granites do not support the presence of a ubiquitous Meso- to Paleo-proterozoic crystalline basement in the study area.A compilation of accurate and precise zircon U-Pb geochronological data shows that many magmatic flare-ups in the inland South China Block (SCB) postdate the Permian-Triassic orogeny, with the most intensive one in Jurassic occurring in a short period of time between 165 Ma and 150 Ma. Although coeval basaltic rocks are volumetrically minor and mantle-derived magmas do not contribute much to the geochemical and isotopic variations in granites at the present level of intrusion, it is believed that underplating and intrusion of mafic magmas into lower crust has acted as the major heat source for the granitic magmatism. The magmatism was most likely triggered by the upwelling of the asthenosphere related to the delamination of flat-subducted oceanic slab and thinning of subcontinental lithosphere.